2022
DOI: 10.1038/s41598-022-23448-7
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characterization and in vitro studies of biological activity of bradykinin derivatives

Abstract: Eleven multiple analogs of bradykinin—a peptide that is a natural ligand of B1 and B2 receptors but does not bind or activate the B1 receptor unless Arg9 is removed from the sequence by the action of carboxypeptidase N—were synthesized. Their biological activity was examined on T-REx cell lines expressing B1 or B2 receptors using the intracellular IP1 assay. The mRNA expression of B1R and B2R in the lysate of tumor cell lines, e.g., U87-MG (human astrocytoma), SHP-77 (human small cell lung cancer), and H4 (hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…These results are very promising, although they partially diverge from the previous antagonistic tests of our analogues. Our study confirms that BK analogues affect the inhibition and growth of colon cancer cells similarly to studies with glioma and lung cancer cells [30].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…These results are very promising, although they partially diverge from the previous antagonistic tests of our analogues. Our study confirms that BK analogues affect the inhibition and growth of colon cancer cells similarly to studies with glioma and lung cancer cells [30].…”
Section: Discussionsupporting
confidence: 84%
“…It has been demonstrated that analogues containing pipecolinic acid with the L-configuration (identical to the native protein amino acid configuration) possess stronger antagonistic activity than with the D-configuration [24,62]. Both of these peptides have also been tested against U87-MG human glioblastoma cells or human lung carcinoma cells and also inhibit the growth of the cancer cell lines, mostly by the B1R receptor [30,63,64]. It is well known that this type of receptor plays an important role in tumour growth, and thus the B1R receptor seems to be a good therapeutic target for novel compounds [65,66].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface-enhanced Raman scattering (SERS) is a highly sensitive, selective, and relatively fast technique that provides information about surface reactions, interfacial charge transfer, and the architecture of the surface-bound molecule-metal complex. It is used for chemical and biological sensing by enhancing the cross-section of Raman scattering from molecules adsorbed on or near the surface of nanostructured materials [61,62]. The enhancement is achieved by plasmon-mediated electric field enhancement or by chemical enhancement [63].…”
Section: Adsorption Monitored By Sersmentioning
confidence: 99%